2014
DOI: 10.1039/c4nr03604b
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic ‘stripping’ and degradation of PEGylated carbon nanotubes

Abstract: Single-walled carbon nanotubes (SWCNTs) coated or functionalized with PEG chains of different molecular weight were assessed for their propensity to undergo biodegradation under in vitro conditions using recombinant myeloperoxidase (MPO) or ex vivo using freshly isolated primary human neutrophils. Our findings suggest that under natural conditions, a combined process of 'stripping' (i.e., defunctionalization) and biodegradation of PEG-SWCNTs might occur and that PEG-SWCNTs are a promising--and degradable--nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 305 publications
(381 reference statements)
2
43
2
Order By: Relevance
“…Using PEG-modified SWCNTs armed with the glucocorticoid-induced TNFR-related receptor (GITR), which has shown higher expression on intratumor versus peripheral regulatory T cells, Sacchetti et al [99] demonstrated in vivo targeting of regulatory T cells residing in a B16 melanoma (skin cancer) in mice. In this context, it is worth noting that innate immune cells can also enzymatically 'digest' PEGylated CNTs [100]. In other words, such CNTs could potentially be handled by the immune system and are therefore promising as vectors for drug or gene delivery in nanomedicine.…”
Section: Nanomaterials and The Adaptive Immune Systemmentioning
confidence: 99%
“…Using PEG-modified SWCNTs armed with the glucocorticoid-induced TNFR-related receptor (GITR), which has shown higher expression on intratumor versus peripheral regulatory T cells, Sacchetti et al [99] demonstrated in vivo targeting of regulatory T cells residing in a B16 melanoma (skin cancer) in mice. In this context, it is worth noting that innate immune cells can also enzymatically 'digest' PEGylated CNTs [100]. In other words, such CNTs could potentially be handled by the immune system and are therefore promising as vectors for drug or gene delivery in nanomedicine.…”
Section: Nanomaterials and The Adaptive Immune Systemmentioning
confidence: 99%
“…Recently, it has been described that oxidized NTs can be digested by activated macrophages via a non-enzymatic peroxynitritepathway, as well as by activated neutrophils and eosinophils via reactive intermediates of myeloperoxidase (MPO) and eosinophil peroxidase, respectively [101][102][103]. Our group has also shown that neutrophils degraded PEG-NTs both intra-and extra-cellularly through the combined activity of neutrophil elastase, which de-PEGylates PEG-NTs, and MPO, which degrades the de-PEGylated NTs 104. Thus, the presence of activated inflammatory cells could facilitate the clearance of PEG-NTs that are introduced into the joints.…”
mentioning
confidence: 85%
“…The outer and inner Fe@MWCNT diameters (ODs and IDs) were nonuniform and varied not only between different but also for particular nanotubes; ODs and IDs were found to be equal to 44 ± 25 and 12 ± 6 nm, respectively. The length of pristine nanotubes was 100±20 m, while oxidation led to their partial cutting and the length was reduced to 50±30 m yielding nanotubes which fall into a biocompatible and water-dispersible category [19][20][21]. Raman spectrum of Fe@MWCNT (Figure 1(c)) shows three dominating signals at 1332, 1579, and 2662 cm −1 which can be assigned to D-(disorder), G-(tangential graphite), and G -(second-order harmonic) bands, respectively [45].…”
Section: Synthesis and Physicochemical Properties Of Nanotubementioning
confidence: 99%
“…On the other hand, today, there is no doubt that short, functionalized with polar moieties, and individualized MWCNTs offer a hope to be tested clinically [16]. But earlier in vitro [17] and in vivo [18] reports confirmed that, after functionalization, even >40 m long Fe@MWCNTs, providing individualized (i.e., not aggregated) nanotubes, could be considered as enzymatically degradable [19,20] and hence excretable drug vehicles [21].…”
Section: Introductionmentioning
confidence: 99%